Modeling the Technological Change and Innovation Activities for Estimation of Productivity Growth - George Korres; Theodoros Iosifides; George Tsobanoglou (European Regional Science Association (ERSA), 2005)
Technological change and innovation activities contribute essentially to the regional dimension and productivity growth. The technological infrastructure and innovation capabilities affect not only the regional growth, but also the whole periphery and economy as well. In the last decades, OECD /introduced some measures and indexes, concerning the Research and Development Expenditures, patents etc., that measuring the innovation activities. However, there are a lot of problems and questions regarding the measurement of innovation activities at a regional level. This paper attempts to analyze the whole framework of innovation and technological activities and in particular to examine the methodological approaches, the appropriate measurement and also the statistical indices for estimation of productivity growth. On this context, it's also aiming to emphasize and to review the appropriate techniques, the most common methods and to analyze the particular methodological and statistical problems.
Keywords: 330